The Effect of Audit Lag, Audit Fee and Size of Public Accounting Firm on Audit Opinion with Going Concern Notes with Company Size as a Moderating Variable - Bilqisth Natasya Febriyanti; Ratih Kususmastuti; Rahayu (Greenation Research & Yayasan Global Resarch National, 2025)
This study aims to examine the effect of audit lag, audit fee, and size of the Public Accounting Firm (KAP) on audit opinion with a going concern note, with company size as a moderating variable. The object of research is energy sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2020-2023. The data used is secondary data from financial reports and independent auditor reports, with a total of 57 samples and 228 observations selected through purposive sampling. The analysis method used is logistic regression and Moderated Regression Analysis (MRA) with the help of SPSS version 30. The results of this study indicate that audit lag, audit fee, and KAP size simultaneously affect audit opinion with a going concern note. Partially, only audit fees have a significant positive effect. Meanwhile, audit lag and KAP size have no significant effect, and company size is unable to moderate the effect of the three on audit opinion with a going concern note.